Impact of leadership behaviour on employee well-being: the case of higher education sector in Pakistan - Kazim, Wajiha (2022)
This doctoral research examines the process of how leadership behaviour influences employee well-being (EWB). Leaders via their behaviour influence subordinates/ followers, which in turn influences their well-being. A critical examination of current research on leadership shows a narrow perspective, which either considers leader or follower opinion, rather than both, in examining leadership. This particularly limits research examining the impact of leadership on organisational outcomes. Therefore, this research focuses on different loci of leadership (leader and subordinate) (Eberly et al., 2013) in relation to EWB. Furthermore, considering the importance of context, this research also examines the impact of multi-level contextual factors, both omnibus and discrete ones (Johns, 2006) on leadership behaviour and EWB. Recent research conceptualises EWB as a broad construct and a consequence of psychosocial factors at work, i.e. how work is managed and organised. Psychosocial factors have been defined as aspects of the design and management of work, and its social and organisational contexts that have the potential for causing psychological or physical harm (Cox and Griffith, 2005). These psychosocial factors can be job stressors or enablers of engagement and are arguably controlled by leaders. Furthermore, EWB also depends on leadership, more precisely, on leader behaviour (Inceoglu et al., 2018). Although different leadership styles have been studied extensively, their relationship with psychosocial factors and EWB has not been investigated in depth. Drawing on job demands resource theory (Demerouti et al., 2001) this research categorises psychosocial factors as job demands and job resources to assess their relationship with EWB. The research is based on study of higher education institutions in Pakistan, where an explanatory sequential mixed methods approach is followed. Overall, this research is divided into three studies. First, a quantitative study is used to examine the relationship between leadership behaviour, job demands, job resources, and EWB. The second study based on semi-structured interviews, provides further explanation of the relationship between EWB and leadership. Research participants in first two studies are faculty members working as lecturer, assistant professor, associate professor, and professors in different higher education institutions of Pakistan. Lastly, the third study is based on interviews with leaders (head/chairpersons of the various departments in different HEIs). The purpose of third study is to get the perspective of leaders on the phenomenon understudy, also to identify relevant contextual factors. The findings clearly suggest that leaders have an immediate effect on EWB, as leaders largely control job demands and job resources. Furthermore, the results explain the importance influence of multi-level contextual factors. Macro-level/omnibus contextual factors not only affect regulatory agency and policy framework of higher education institutions, but also psychosocial factors, leadership behaviour, choices leaders make while implementing various policies, and EWB. For example, social, legal, economic, political, and technological factors do play key role in framing policies and regulations at the discrete level, but implementation of those policies and regulations rests with the leader. These results from two different perspectives are discussed from an integrative perspective to uncover the broader spectrum of leadership influence process, and to avoid the implications of self-serving bias (Bradley, 1978). These perspectives also highlighted the underlying mechanisms that strengthen the impact of leadership behaviour on EWB. Limitations and avenues for future research are also identified and discussed in the discussion chapter.